POTENSI EKSTRAK JAHE MERAH (Zingiberaceae officinale rosc)SEBAGAI ANTIMIKROBA DAN PENINGKAT KUALITAS SPERMATOZOA MENCIT YANG DIINFEKSI BAKTERI Staphylococcus aureus SECARA INTRA URETHRA - ersanto, Ersanto; Sukarjati, Sukarjati (WAHANA, 2017)
Red Ginger (Zingiberaceae officinale rosc) is known to be used as an anti-microbial andenhancing the quality of spermatozoa. This study aims to demonstrate of the red ginger extract(Zingiberaceae officinale rosc)potential as an antimicrobial and the quality enhancer of spermatozoain laboratory rats injected by Staphylococcus aureus to its urethra. The red ginger was extracted byethanol. The sample of this research was the spermatozoa of 30 mice that were injected byStaphylococcus aureus to its urethra. Potential test of red ginger extract on the laboratory ratsconducted by observing the spermatozoa’s motility, viability, morphology, the spermatozoa’sconcentration and the amount of spermatozoa leukocyte in the laboratory rats after the administrationof the red ginger extract for 35 days under the microscope. Antimicrobial activity test onStaphylococcus aureus was done by culturing the spermatozoa of laboratory rats (in vivo) afteradministering the red ginger extract for 35 days with total plate count method. The result of the studyshowed that there were differences between negative control group of laboratory rats and positivecontrol group of laboratory rats (laboratory rats injected with Staphylococcus aureus intra urethra)motility (p = 0.000), viability (p = 0.000), morphology (p = 0.000), concentration (p = 0.000), and theamount of leukocyte (p = 0.000). Whereas on the calculation of red ginger extract bacterial coloniesgive the significant effects p <0.05 on the growth of S. aureus. Based on the results of this study, it canbe conclude that the red ginger has potential as an antimicrobial and it also can improve the quality ofspermatozoa in laboratory rats infected with S. aureus through its urethra.